2000
DOI: 10.1037/1099-9809.6.4.334
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural evaluation of ethnic perspective-taking ability: An exploratory investigation with U. S. Latino and Guatemalan Ladino children.

Abstract: Children's development of ethnic perspective-taking ability (EPTA) was evaluated across 2 samples. It was hypothesized that the EPTA construct would be related to ethnic cognitions (e.g., ethnic knowledge, ethnic self-identification) and nonethnic cognition (i.e., social cognition) and that there would be variance in the EPTA construct distinct from a closely related form of social perspective-taking ability (SPTA). In Sample 1, 2nd- and 6th-grade Latino children (i.e., children of Mexican descent in the Unite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 37 publications
4
14
0
Order By: Relevance
“…When combined with egocentric induction, perception of greater similarity to in-group members results in greater attraction and more positive feelings toward the in-group. This is consistent with the observation that intergroup bias often focuses on in-group evaluations rather than out-group evaluations (Aboud, 2003;Brewer, 1999;Nesdale, 2008), and that ethnic perspective taking may be associated with lower ethnic prejudice (Quintana, 1998(Quintana, , 1999(Quintana, , 2007Quintana, Ybarra, Gonzalez-Doupe, & de Baessa, 2000).…”
Section: Egocentric Social Projection As a Basis For Intergroup Biassupporting
confidence: 89%
See 1 more Smart Citation
“…When combined with egocentric induction, perception of greater similarity to in-group members results in greater attraction and more positive feelings toward the in-group. This is consistent with the observation that intergroup bias often focuses on in-group evaluations rather than out-group evaluations (Aboud, 2003;Brewer, 1999;Nesdale, 2008), and that ethnic perspective taking may be associated with lower ethnic prejudice (Quintana, 1998(Quintana, , 1999(Quintana, , 2007Quintana, Ybarra, Gonzalez-Doupe, & de Baessa, 2000).…”
Section: Egocentric Social Projection As a Basis For Intergroup Biassupporting
confidence: 89%
“…Might perspective taking be similarly implicated in the context of real groups? Quintana et al. (2000) and Quintana (2007) found that ethnic perspective‐taking ability maps onto social perspective‐taking ability, increasing especially between the ages of 6 and 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of ethnicity, Quintana and colleagues recently found that ethnic perspective-taking ability was associated significantly not simply with general social perspective-taking ability but also with 'ethnic cognition' (i.e. knowledge and self-identification) at similar ages (US second grade) (Quintana, Ybarra, Gonzalez-Doupe, & De-Baessa, 2000). This, in line with the age-7 peak in ethnic-role development, can go to explain the unique pattern we found for ethnocentric reasoning.…”
Section: Discussionsupporting
confidence: 52%
“…Transracially adoptive mothers' cultural socialization/pluralism may also be guided by agerelated increases in their children's understanding of their adoptive status. Preparation for bias may be even more likely to be influenced by children's age and understanding of race (Hughes & Chen, 1999;Rojewski, 2005), both of which make important advances in middle childhood and adolescence (e.g., Aboud, 1988;Lee & Quintana, 2005;McKown & Weinstein, 2003;Quintana, Ybarra, Gonzalez-Doupe, & De Baessa, 2000).…”
Section: Child Predictors Of Racial Ethnic and Cultural Socializatimentioning
confidence: 99%